The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.virol.2009.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Maternal neutralizing antibodies against a CRF01_AE primary isolate are associated with a low rate of intrapartum HIV-1 transmission

Abstract: Mother-to-child transmission (MTCT) of HIV-1 provides a model for studying the role of passively acquired antibodies in preventing HIV infection. We determined the titers of neutralizing antibodies (NAbs) against six primary isolates of clades B and CRF01_AE in sera from 45 transmitting and 45 nontransmitting mothers matched for the main independent factors associated with MTCT in Thailand. A lower risk of MTCT, particularly for intrapartum transmission, was associated only with higher NAb titers against the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 26 publications
4
21
1
Order By: Relevance
“…To investigate to what extent the V1V2 domain might contribute to the particular resistance of clone 11005CL7 to 2G12, we constructed two chimeric env genes in which the V1V2 domains of 11005CL7 and 5008CL2 were swapped using a domain exchange strategy, as previously described (28,30). The chimeric 5008CL2env⌬V1V2[V1V2 11005CL7 ] (CHIM1) expressed the V1V2 domain of 11005CL7 in the 5008CL2 env backbone, whereas the chimeric 11005CL7env⌬V1V2 [V1V2 5008CL2 ] (CHIM2) expressed the V1V2 domain of 5008CL2 in the 11005CL7 recipient env (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate to what extent the V1V2 domain might contribute to the particular resistance of clone 11005CL7 to 2G12, we constructed two chimeric env genes in which the V1V2 domains of 11005CL7 and 5008CL2 were swapped using a domain exchange strategy, as previously described (28,30). The chimeric 5008CL2env⌬V1V2[V1V2 11005CL7 ] (CHIM1) expressed the V1V2 domain of 11005CL7 in the 5008CL2 env backbone, whereas the chimeric 11005CL7env⌬V1V2 [V1V2 5008CL2 ] (CHIM2) expressed the V1V2 domain of 5008CL2 in the 11005CL7 recipient env (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2A). Recent studies on CRF01_AE (40,47) and subtype C Env (39) showed that viral susceptibility to neutralizing antibodies was inversely correlated with the length of V1 and V2 regions of Env gp120. In addition, several CRF01_AE Env clones that contain a long V2 region, similar to 65CC1 (46), were resistant to b12-mediated neutralization (47).…”
Section: Resultsmentioning
confidence: 99%
“…In a Thai study of maternal antibodies and MTCT, there was evidence that the neutralizing potential against one particular regional HIV-1 strain was correlated with infant infection (2,43). It is difficult to compare these studies directly because the prior study examined antibodies in the maternal index case, while ours focused on antibodies in the exposed infant.…”
Section: Discussionmentioning
confidence: 97%
“…Several early studies, each relatively small, showed that nontransmitting mothers had more frequently detected and/or higher levels of NAb responses than transmitting mothers, suggesting a role for NAb in reducing MTCT (7,16,22,45,46). A correlation between maternal antibodies and transmission risk was also observed in a larger study of Thai women (n ϭ 90), in which the potency of NAb responses to 2 of 4 viruses tested inversely correlated with transmission (2,43). Subsequent studies showed that the variants transmitted to infants tended to be those in the mother that were the most resistant to NAbs (10,51).…”
mentioning
confidence: 78%